2010
DOI: 10.1093/icesjms/fsq111
|View full text |Cite
|
Sign up to set email alerts
|

Gonad maturation in Octopus vulgaris during ongrowing, under different conditions of sex ratio

Abstract: Estefanell, J., Socorro, J., Roo, F. J., Fernández-Palacios, H., and Izquierdo, M. 2010. Gonad maturation in Octopus vulgaris during ongrowing, under different conditions of sex ratio. – ICES Journal of Marine Science, 67: 1487–1493. Octopus vulgaris is a suitable candidate for aquaculture, but there are problems with breeding in captivity, such as aggressive behaviour among males and the frequent death of females after the eggs hatch. To avoid these problems and further understand the sexual maturation of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
2
19
0
1
Order By: Relevance
“…Prior to the beginning of this trial, males and females were separated upon arrival to our facilities, so sexual interaction probably occurred in nature or most likely in the trawl, where octopus may be kept for a few days until transport to lab facilities. Also, low DGI in comparison with octopus reared in Trial 1 is related to poor condition (Cerezo Valverde et al 2008; Estefanell et al 2010).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Prior to the beginning of this trial, males and females were separated upon arrival to our facilities, so sexual interaction probably occurred in nature or most likely in the trawl, where octopus may be kept for a few days until transport to lab facilities. Also, low DGI in comparison with octopus reared in Trial 1 is related to poor condition (Cerezo Valverde et al 2008; Estefanell et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Particularly in Trial 1, low growth rates observed in females and the presence of egg masses evidenced reproductive behavior (Iglesias et al 2000), which is associated to the end of O. vulgaris life cycle in both sexes (Estefanell et al 2010). Also, different growth rate and final weight between sexes led to high weight dispersion, which also increases mortality in O. vulgaris under rearing conditions, due to hierarchical behavior and cannibalism (Socorro et al 2005; García García et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common octopus (Octopus vulgaris, Cuvier 1797) is a prime candidate for diversification of marine aquaculture, and extensive research efforts have been devoted over the last decade to investigate several aspects of octopus culture including husbandry (Iglesias et al 2006), reproduction (Estefanell et al 2010;Otero et al 2007;Wodinsky 2008) and nutrition Villanueva 2000, 2003;Quintana 2009;Villanueva et al 2009). Although considerable progress has been made and on-growing wild-captured octopus in floating cages is now possible (Iglesias et al 2007), a major, yet unresolved, problem in octopus culture is the high mortality of paralarvae, early pelagic life stages, which massively die during metamorphosis to benthic life stages, and consequently, the octopus life cycle in captivity has not yet been closed.…”
Section: Introductionmentioning
confidence: 99%
“…Increased mortality associated with reproductive processes has been observed under rearing conditions in both sexes (Estefanell et al . ). In contrast, several authors reported a high biological performance in males and females of O. vulgaris reared together in floating cages (Rodríguez et al .…”
Section: Introductionmentioning
confidence: 97%